Building data centers using Network Attached Storage (NAS) and Microprocessor Operating Systems. Issue 1 (February 2021) - Andriani, Titi; Hidayatullah, Muhammad; Saputra, Dekky; Esabella, Shinta; Gunawan, G
Abstract: Computer Laboratory of the University of Technology Sumbawa still does not have a Data Center, in the process of learning and teaching experiencing several obstacles one of which is the difficulty in sharing files between computers. The research objective is to build a Data Center at the Computer Laboratory of the University of Technology Sumbawa with the aim of facilitating practicum participants in sharing files between computer system devices. The method used in this research is the network development method Prepare, Plan, design, Implement, Operate, Optimize (PPDIOO). The results of NAS tests on different devices give results that are file access connections via wireless and LAN can run well and by producing Data Centers at the Computer Laboratory of the University of Technology Sumbawa can facilitate the process of storing cheap and efficient data.